2017
DOI: 10.1016/j.tpb.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Fisher–Wright model with deterministic seed bank and selection

Abstract: Seed banks are a common characteristics to many plant species, which allow storage of genetic diversity in the soil as dormant seeds for various periods of time. We investigate an above-ground population following a Fisher-Wright model with selection coupled with a deterministic seed bank assuming the length of the seed bank is kept constant and the number of seeds is large. To assess the combined impact of seed banks and selection on genetic diversity, we derive a general diffusion model. The applied techniqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 55 publications
11
69
0
Order By: Relevance
“…To test this hypothesis, we simulated the trajectory of a beneficial allele in a population subject to the strong seed-bank effect and examined the dormant and active portions of the population separately (see Supplemental Materials: Selection simulation). As expected, we found that the average amount of time required for a beneficial allele to reach fixation increases with the average number of generations that an individual spends in the seed bank (Figure 4a,b) (Koopmann et al, 2017).…”
Section: Selectionsupporting
confidence: 82%
See 2 more Smart Citations
“…To test this hypothesis, we simulated the trajectory of a beneficial allele in a population subject to the strong seed-bank effect and examined the dormant and active portions of the population separately (see Supplemental Materials: Selection simulation). As expected, we found that the average amount of time required for a beneficial allele to reach fixation increases with the average number of generations that an individual spends in the seed bank (Figure 4a,b) (Koopmann et al, 2017).…”
Section: Selectionsupporting
confidence: 82%
“…In a population with a seed bank, there are active and dormant subpopulations, where individuals enter and exit a dormant state in a manner analogous to migration between subpopulations (Blath, González-Casanova, Eldon, Kurt, & Wilke-Berenguer, 2015;Lennon & Jones, 2011) (Figure 1). Seed banks are sometimes viewed simply as an evolutionary buffer (Koopmann, Müller, Tellier, & Živković, 2017). Dormancy preserves existing genetic diversity by decreasing the rate that genetic diversity is removed from the population (Hairston & De Stasio, 1988;Koopmann et al, 2017;Vitalis, Glémin, & Olivieri, 2004), in turn increasing in the effective size of the population (Nunney, 2002).…”
Section: Population Genetic Consequences Of Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested early on that due to the storage effect, seed banking slows down the action of selection (Templeton & Levin, 1979;Hairston & De Stasio, 1988). Recent theory shows that a positively (negatively) selected allele has indeed a longer time to fixation (loss) under a persistent seed bank, but only by a factor 1/b compared with 1/b² for neutral alleles (Koopmann et al, 2017) because plants are exposed to selection in the above-ground population as soon as the seeds germinate (with probability b). In other words, more persistent seed banks effectively: (1) slow down the time of fixation of advantageous alleles; but (2) decrease the probability for these alleles to be lost due to random drift (Koopmann et al, 2017;Shoemaker & Lennon, 2018).…”
Section: Seed Banks Influence the Rate And Signatures Of Natural mentioning
confidence: 99%
“…Furthermore, neglecting seed banks may yield distorted results for the inference of past demography using for example the SFS (Živković and Tellier, 2012). Interestingly, the effect of (weak) selection is enhanced by the slow-down of the time scale due to seed banks (Blath et al, 2013(Blath et al, , 2016Koopmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%